A case of meropenem-induced liver injury and jaundice. Issue 1 (2nd January 2021) - Cheung, Szeya; Bulovic, Jennifer; Pillai, Ajish; Manoj, Trehan; Neeraj, Katriyar
ABSTRACT: This report describes what we believe is the first reported case of clinically significant cholestasis and acute liver injury within three days of meropenem therapy. An 83-year-old Hispanic female was admitted for sepsis of unknown origin and was started on intravenous meropenem. Three days following initiation of the antibiotic, the patient developed mixed hepatocellular and cholestatic liver injury with jaundice and pruritus. Possible causes of cholestasis were excluded after extensive investigations. A drug-induced liver injury was suspected and meropenem was discontinued. Following discontinuation of meropenem, the patient demonstrated symptomatic and laboratory improvements, and her liver enzymes and bilirubin levels were normalized.